Peran Lingkungan Sekolah dalam Mengatasi Perilaku Bullying pada Siswa Kelas V di SDN Muruy 2 Kecamatan Menes - Suci Dwi Handayani; Hanafiah Hanafiah; Irvan Fariji; Imay Maesaroh (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
From an early age, basic education plays a crucial role in shaping a child's character and personality. However, bullying is becoming increasingly common, including at the elementary school level. This study focused on fifth-grade students at Muruy 2 Elementary School in Menes District to identify the forms of bullying that occur, the contributing factors, and the school's role in addressing it. Initial observations and interviews indicated that bullying often takes the form of teasing, exclusion, and verbal abuse. This negatively impacts students' mental health and learning motivation. A less responsive school environment tends to exacerbate the situation. The study, conducted from April–July 2025, used a qualitative approach with a case study method. Data were collected through observation, documentation, and interviews with students in the 2025/2026 academic year. The primary objective was to determine teachers' strategies for dealing with bullying. The findings revealed that bullying most often occurs verbally and physically, such as teasing, pushing, hitting, or disturbing friends while studying. Victims are generally shy, quiet, or physically weak, while perpetrators tend to be low-achieving and have prominent physical characteristics. Bullying typically occurs in classrooms or other less-supervised school areas. Its impacts are widespread, ranging from declining academic performance to psychological distress for both victims and perpetrators, as well as the surrounding community. Driving factors include peer pressure and personal circumstances. Despite still facing obstacles such as limited supervision and a lack of parental involvement, the school strives to enforce rules and build cooperation among stakeholders. This study aims to provide a descriptive overview of bullying behavior at Muruy 2 Elementary School, Menes District, as well as the causes, characteristics, and role of schools in eradicating it.